Effect of the Number of Nozzles of Swirl Flow Generator Utilized in Flat Plate Solar Collector: An Entropic Analysis - Yan Cao; Hamdi Ayed; Tuqa Abdulrazzaq; Taza Gul; Abdul Bariq; Belgacem Bouallegue (International Journal of Photoenergy)
The numerical model of the pipes of a flat plate solar collector (FPSC) with several nozzles has been investigated in the present study. Indeed, the effect of the number of nozzles of the swirl generator on the entropic characteristics has been evaluated. The nozzles were applied for improving the performance of FPSC. For evaluating the proposed system based on the entropy concept, the effect of injection angle and mass flow rate has been considered. The selected injection angles were 30°, 45°, 60°, and 90°. Also, the total mass flow rates entered from all of the nozzles were 0.2 kg/s, 1 kg/s, and 2 kg/s. The effect of said variables on frictional and thermal entropy generations was analyzed; then, the overall energetic-entropic performance of the system was predicted using several dimensionless parameters including NE, NS, Nu∗, and heat transfer improvement (HTI). Moreover, Witte-Shamsundar efficiency (ηW−S) was applied to pinpoint the efficiency of the system. The highest value of HTI and ηW−S was 1.7 and 0.9 that achieved by “single-nozzle; A90-D50-N12.5-M0.2” and “quad-nozzle; A30-D50-N12.5-M2,” respectively.